The Effect of Augmented Reality Applications Integrated with Modeling on Pre-Service Science Teachers' Modeling Skills and Academic Achievements - Nesrin Ürün Arıcı; Ümit Şimşek (Universitas Pendidikan Indonesia, 2023)
This study investigates the impacts of augmented reality applications integrated with modeling on pre-service science teachers' modeling skills achievements and determines their opinions toward the implementation process. This study used a simultaneous nested mixed method in which two online and face-to-face groups of fifty-six first-year pre-service science teachers were randomly assigned to the experimental groups. The